THE RULING ON THE USE OF SALBUTAMOL INHALER FOR PEOPLE WHO FAST ACCORDING TO 'ABDUL 'AZĪZ IBN BĀZ AND WAHBAH AL-ZUḤAILĪ (A COMPARATIVE STUDY) - Puteri, Andi Indra; Salenda, Kasjim; Sohrah, Sohrah (International Journal of Islamic Studies, 2022)
Performing fasting in the holy month of Ramadan is an obligation of every Muslim. Muslims who fast are given a great reward in the sight of Allah swt. To achieve this great reward, fasting by obeying the rules and regulations is a necessity. True fasting is fasting in accordance with the guidance of the Prophet saw. There are obligations that must be done, there are sunnahs that must be maintained, and there are also prohibitions that should be avoided. Allah swt. has prescribed fasting with restrictions that if violated can invalidate the fast. So it is obligatory for every Muslim to know all the things that can invalidate his fast so that he can carry out fasting properly according to sharia guidance. In this modern era, along with the development of the times, there are many things that are disputed by the scholars, whether they are included in breaking the fast or not, such as modern medical / health equipment, including "salbutamol inhaler" which is commonly used by people who are suffering from lung and respiratory diseases. The Mufti of Saudi Arabia, Abdul 'Azīz ibn Bāz, stated in his fatwa that it is permissible to use asthma inhalers while fasting. The Syrian mufti Wahbah al-Zuḥailī, on the other hand, is of the opinion that asthma inhalers invalidate the fast.